Common Coherence Witnesses and Common Coherent States - Bang-Hai Wang; Zi-Heng Ding; Zhihao Ma; Shao-Ming Fei (Entropy, 2021)
We show the properties and characterization of coherence witnesses. We show methods for constructing coherence witnesses for an arbitrary coherent state. We investigate the problem of finding common coherence witnesses for certain class of states. We show that finitely many different witnesses <semantics>W1,W2,⋯,Wn</semantics> can detect some common coherent states if and only if <semantics><msubsup>∑i=1n</msubsup>tiWi</semantics> is still a witnesses for any nonnegative numbers <semantics>ti(i=1,2,⋯,n)</semantics>. We show coherent states play the role of high-level witnesses. Thus, the common state problem is changed into the question of when different high-level witnesses (coherent states) can detect the same coherence witnesses. Moreover, we show a coherent state and its robust state have no common coherence witness and give a general way to construct optimal coherence witnesses for any comparable states.